2016
DOI: 10.1007/s13351-016-5164-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in studies of cloud overlap and its radiative transfer in climate models

Abstract: The latest advances in studies on the treatment of cloud overlap and its radiative transfer in global climate models are summarized. Developments with respect to this internationally challenging problem are described from aspects such as the design of cloud overlap assumptions, the realization of cloud overlap assumptions within climate models, and the data and methods used to obtain consistent observations of cloud overlap structure and radiative transfer in overlapping clouds. To date, there has been an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…One important aspect of CF is the vertical overlap, which has significant implications to cloud radiative effects (e.g., Liang & Wang, 1997; X. Wang et al., 2021; H. Zhang & Jing, 2016). As shown by F. Zhang et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One important aspect of CF is the vertical overlap, which has significant implications to cloud radiative effects (e.g., Liang & Wang, 1997; X. Wang et al., 2021; H. Zhang & Jing, 2016). As shown by F. Zhang et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous studies found that the low–level water vapor over the SETP in summer mainly depends on the transport of the warm and humid air over the Indian Ocean and the Bay of Bengal, while the upper–level wind and water vapor are under the influence of South Asian High (SAH) (Xu, 2015; Zhang & Jing, 2016). These features are well reflected in this study as the low–level is dominated by southwesterly wind and convergence of water vapor (Figure 5d) and the upper–level is dominated by northwesterly wind and divergence of water vapor (Figure 5a) in mean summer state.…”
Section: Formation Mechanism Of the Summertime Cvs Over The Setpmentioning
confidence: 99%
“…Among different CVSs, multi–layer cloud structure and single–layer cloud structure are two distinctive CVSs and have different radiation effects. With higher CTH, multi–layer clouds usually reflect less sunlight to the top of the atmosphere and transmits more energy to the surface compared with single–layer clouds (Li et al., 2011; Zhang & Jing, 2016). Multi–layer cloud is most important for keeping the energy balance at the top of the atmosphere (Lü et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the spread degree of OLR (LWCRE) is very large over SA (Figures 5f and 8f), reflecting that various simulated convection intensity and distribution occur in CMIP6 AMIP models. Note that although the absolute contribution of LWCRE to NCRE is relatively small over SA (Table 4), the spread degree of simulated LWCRE is very large over EC where current climate models probably have big differences in reproducing cloud height and cloud vertical distribution (H. Zhang & Jing, 2016). Moreover, clear‐sky components also substantially contribute to the CRE biases (Figures , , , and ).…”
Section: Annual Mean Statesmentioning
confidence: 99%